PENGARUH VARIASI JARAK PITCH SUDU TURBIN SCREW PADA KEMIRINGAN LINTASAN 45° TERHADAP OUTPUT DAYA - Muhammad Ghiffary Zain; Arif Setyo Nugroho (Teknika, 2026)
This study investigates how changes in the pitch distance of the screw turbine blades at an orbital tilt angle of 45° affect power output. The Archimedean screw turbine is a promising technology for small-scale hydropower generation, but further research is still needed to optimize its design. This research focuses on two main parameters: pitch blade and pitch track 45°. The research methods include laboratory and field-scale simulations with pitch variations of 130 mm, 150 mm, and 100 mm. Measurements of power and turbine efficiency have been conducted. Data analysis used descriptive and inferential statistical techniques, including analysis of variance (ANOVA) to test the significance of differences between pitch distance variations, and regression analysis to model the relationship between pitch distance and turbine performance parameters. The research shows that a pitch of 150 mm provides optimal performance. At DC load, a maximum torque of 15.2 Nm, a maximum output of 750 W, a maximum turbine efficiency of 82%, and a maximum PLTMH efficiency of 75% are achieved. Meanwhile, at AC load, a maximum torque of 14.8 Nm and a maximum output of 72 are achieved.